Functional Outcome of Sesamoid Excision in Athletes. Issue 3 (24th March 2016) - Coetzee, J. Chris; Stone, Rebecca M.; Fritz, Jacquelyn E.; Grossi, Emma F.
Objectives: Sesamoid issues can have a significantly negative impact on the ability of athletes of all levels to return to play. Conventional treatments include rest, physical therapy (PT), shoe modifications and orthotics. Even with adequate conservative care there are a number of patients who continue to have chronic pain and inability to perform. The literature shows mixed results with sesamoid excisions and ability to return to play. The hypothesis of the study was that with proper surgical technique of sesamoid excisions and adequate rehabilitation, there is a reasonably probability to return to the previous level of sporting activity. Methods: All athletes presented to the clinic with the diagnosis of sesamoid pain were followed. After approval by the Institutional Review Board, we reviewed only the patients whose symptoms did not resolve. Exclusion criteria included any neurologic deficit or diabetes. Between January 2006 and December 2013, excision of the medial, lateral or both sesamoids was performed for 89 feet in 80 patients (68 females and 12 males). The mean age was 46.25 years old (range 14.1-79.6). All patients had serial x-rays done during the conservative part of their treatment and at least one MRI to confirm the diagnosis of osteochondrosis or chronic injury to the sesamoid. Medial sesamoids were excised through a medial approach, while lateral sesamoids through a plantar approach. Care was taken to adequately repair the plantar structures after excision. A structured post-operative protocol was followed to ensure stability of the plantar plate/sesamoid complex and a gradual return to play over 6 months. A graphite plate was used to limit dorsiflexion for the first 6 months. Outcomes were evaluated pre and postoperatively with the VR-12 Mental and Physical Scores, Revised Foot Function Index (FFI-R), VAS scoring and patient satisfaction. Results: Eight patients had sesamoid excisions in both feet; fifty-two patients were medial excisions and 18 were lateral sesamoid excisions. Three patients (3 feet) were lost to follow-up; therefore 77 Patients, 86 feet were followed and are reported on. At a mean follow up of 39.72 months [11 months to 9 years (108.4 months) the mean outcome for VR-12 Mental and VR-12 Physical score were insignificant. The FFI-R improved from pre-operative to post-operative, 129.8 to 58.76, respectively. The VAS also improved dropping from 5.06 to 3.05, pre-operatively to post-operatively. One patient had chronic pain and instability and required a fusion. Two patients developed symptomatic hallux valgus deformities that required a surgical repair. There were no cock-up deformities. Of the 77 patients 66 (86%) could return to their previous sporting activity. Two of the 4 bilateral sesamoid excision patients did not return to the previous level of activity. 25% of patients still report some pain, but not enough to limit their activity level. Conclusion: Chronic sesamoid pain is difficult to treat, but this study confirms prior reports that with meticulous surgical technique, and a dedicated post-operative rehabilitation program, the likelihood of returning to the previous level of sporting activity is high. The outcomes score also confirm a significant improvement in functional parameters.